Food Production in the Cities of Tomorrow. The Results of International Questionnaire Surveys - Burchard‑Dziubińska, Małgorzata (Comparative economic research. Central and Eastern Europe, 2023)
The considerations in this article have three goals. The first is to obtain information on the practical experience of young urban residents who use urban horticulture and agriculture products. The second is to determine the readiness to practice such production independently in the future. The third is to identify the environmental benefits (ecosystem services) related to urban horticulture and agriculture indicated by the respondents. In this case, it was about examining the “environmental intuition” of people who are not professionally related to natural and agricultural sciences. The comparative study concerned students from Brazil, China, India, Mexico, Poland, and a group of seven countries from the European Union. In total, respondents came from 29 countries. The collected data were used to compare the approach to urban horticulture and agriculture and their produce represented by respondents from different countries and cultural circles and to formulate conclusions on how to use the related potential to support sustainable urban development.